A History of Judaism - Goodman, Martin, 1953- (Book collections on Project MUSE., 2018)
"Judaism is one of the oldest religions in the world, and it has preserved its distinctive identity despite the extraordinarily diverse forms and beliefs it has embodied over the course of more than three millennia. A History of Judaism provides the first truly comprehensive look in one volume at how this great religion came to be, how it has evolved from one age to the next, and how its various strains, sects, and traditions have related to each other. In this magisterial and elegantly written book, Martin Goodman takes readers from Judaism's origins in the polytheistic world of the second and first millennia BCE to the temple cult at the time of Jesus. He tells the stories of the rabbis, mystics, and messiahs of the medieval and early modern periods and guides us through the many varieties of Judaism today. Goodman's compelling narrative spans the globe, from the Middle East, Europe, and America to North Africa, China, and India. He explains the institutions and ideas on which all forms of Judaism are based, and masterfully weaves together the different threads of doctrinal and philosophical debate that run throughout its history."--